Radiation protection and natural building materials in cultural heritage - La Verde, Giuseppe; Ricciardelli, Alessio; Ognibene, Elisa; Ambrosino, Fabrizio; Pugliese, Mariagabriella (Frontiers in Built Environment, 2024)
IntroductionBuildings that constitute cultural heritage and that are the identity of a defined geographical area are increasingly being restored to offer the community historical places to enjoy. Often the restoration preserves the original structure and building materials, which are usually natural stones. In this study, a radioprotection protocol dedicated to this kind of built environment was proposed and validated.MethodsAfter identifying the two predominant types of building material stones (Rosso ammonitico and Pietra Serena), radiometric measurements for natural gamma-emitting radionuclides (Ra-226, Th-232, and K-40) and measurements of the emanation coefficient and calculation of the exhalation rate of radon gas were carried out.ResultsThe two types of stone have a content of natural radionuclides that do not exceed the levels recommended by the regulations. The difference between the two types of stone is of an order of magnitude indicating that the red ammonite has a greater radiological impact than the pietra serena.DiscussionThe results, in addition to ensuring the radioprotection of the population, highlighted the need to increase the number of this kind of investigations to implement scientific knowledge and serve the stakeholders involved.